PENGARUH TERPAAN POP UP IKLAN "WAKTU INDONESIA BELANJA" PADA PLATFORM YOUTUBE TERHADAP LOYALITAS PELANGGAN TOKOPEDIA(Survei Pada Pelanggan Tokopedia di Wilayah Kramat Jati, Jakarta Timur) - Qeis Hibaturrahman (2021)
This study discusses the effect of exposure to pop up advertisements "Indonesia Shopping Time on the Yotutube Platform on Tokopedia Customer Loyalty. The purpose of this study was to determine whether there was an effect of exposure to pop up advertisements "Indonesia Shopping Time" on the Yottube version of the platform on Tokopedia customer loyalty, and to find out how big the influence was. The theory used in this research is the Elaboration Possibility Theory. The method used is a quantitative research method. Data collection is done by distributing questionnaires. The population in this study were Tokopedia customers in the Kramat Jati area, for the sample using the Lemeshow formula which was then obtained as many as 96 respondents. The sampling technique used in this study is a purposive sampling technique. Data processing in this study using SPSS version 25 for Windows. Based on the results of the calculation of the coefficient of determination, it was found that the effect of advertising exposure on customer loyalty was 32.1%, while the remaining 67.9% was influenced by other variables not examined in this study. The results of hypothesis testing using the t test show that t count 6.646 > t table 1.665, it can be concluded that H0 is rejected and Ha is accepted. The R value obtained through the correlation test of 0.567 which is in the category of correlation coefficient interpretation value shows a fairly strong level of influence. So, it can be seen and concluded that exposure to pop up advertisements "Indonesian Shopping Time" on the Yotutube Platform has a strong enough influence on Tokopedia customer loyalty to Tokopedia customers in the Kramat Jati area.